DETERMINATION OF SUITABLE RHEOLOGICAL MODEL FOR POLYETHYLENE GLYCOLS AND SILICA PARTICLE MIXTURES - Yanen, Cenk; Aydoğmuş, Ercan; Solmaz, Murat Yavuz (My University, 2020)
Shear thickening fluids are smart materials that show a sudden increase in viscositywhen exceeding critical shear rates. Different theories have been proposed to explain theseproperties of shear thickening. The most used of these theories are Order-Disorder Transition andHydro-Cluster Theory. Due to their reversible properties, shear thickening fluids have been usedin many areas. High molecular weight polyethylene glycols showed faster shear thickening fluidsbehavior. The molecular weight of polyethylene glycol affects many parameters. These parametersare physical bonds, aggregations of molecular, solid particle interactions, and functional groupsin the chain. Due to their effect, rheological behaviors of low and high molecular weightpolyethylene glycols differ. The mixtures of polyethylene glycols and fumed silica particles show acolloidal distribution. The distribution of fumed silica particle molecules in polyethylene glycol,interaction with each other restriction, and movement of the bulks have affected rheologicalproperties. Physical interactions are manifested in the structure. The mixture showed non-Newtonian behavior in the first and second regions as well. Rheological behaviors of mixtures werecompared with experimental data using non-Newtonian models. Power Law, Bingham, Casson,Herschel-Bulkley, and Sisko model equations were used. Silica particle-PEGs mixtures showpseudo plastic in the first region and dilatant fluid behavior in the second region. In the first region,the Power Law model was determined as the most suitable model for experimental data. In thesecond region, the Herschel-Bulkley model was found to be the most suitable model that wasdetermined by statistical analysis.
Keywords: Kimya; Uygulamalı; Polimer Bilimi; Fizikokimya